TPACK-Based E-Textbooks for Science Literacy: A Systematic Review in Primary School Education - Sundari, Fitri Siti; Yufiarti; Bintoro, Totok (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2025)
The purpose of this study is to investigate the need for TPACK-based digital book development in an effort to improve science literacy in primary schools. The study used a systematic review method of 67 domestic and international academic articles published between 2019 and 2025. This research was carried out through the provision of seven main indicators, namely the characteristics of students at the elementary school level, the characteristics of teachers at the elementary school level, the need for digital media and digital books for science learning at the elementary school level, TPACK strategies in learning design, incorporating TPACK into digital books, science literacy as the main goal of science learning, and the use of digital books in education. The results of the analysis showed that students needed interactive, multimodal, and context-specific learning media, while teachers needed detailed TPACK-based training assistance. Furthermore, digital books designed based on TPACK are able to increase students' knowledge of concepts, learning engagement, and learning abilities. These results confirm the fact that TPACK-based digital book design is an innovative solution applied to learning science in primary schools. This study is likely to have an impact on the basis for adaptations, contexts, and effective products on digital science books to enable national learning services.